PENGARUH PENGAWASAN TERHADAP KINERJA GURU PADA SMA PGRI 1 KOTA SUKABUMI - Neni Rosmiati (Universitas Muhammadiyah Jakarta, 2017)
Background of the research, due to the phenomenon that occurs in SMA PGRI 1 Kota Sukabumi, because not yet optimal performance of teachers, which of course caused by several factors, among others is the Effect of Monitoring on Teacher Performance at SMA PGRI 1 Kota Sukabumi. While the focus of the problem in this research is how much influence of supervision on teacher performance in SMA PGRI 1 Kota Sukabumi, The purpose of the research is to be able to know how big Influence Supervision Against Teacher Performance agencies. One of the theoretical foundations in this research According to Siagian (1996: 26) the function of watching is one of the most important management functions that must be done by a leader in an effort to achieve organizational goals he leads. This research uses survey method and the type of research is quantitative descriptive, that is by distributing questionnaires to respondents. A sample of 21 is specified via Saturated Sampling or Census. The data analysis is done quantitatively by using regression statistic formula, either linear or multiple. Then the hypothesis test is done by t test and F test. The results showed that: Partially result of t test indicate that in variable X that Supervision have strong and significant influence to teacher performance (Y), because t arithmetic> t table. Simultaneously tested through Test F has a strong and significant influence on the dependent variable Y (Performance Teacher), because F arithmetic> F table. The variability of Variable Y is influenced by the diversity of variables X. It shows that Su- pervision is needed and always needed to improve Teacher Performance of SMA PGRI 1 Kota Sukabu- mi. From the results of the study can be concluded that the influence of supervision of teachers in SMA PGRI 1 Kota Sukabumi supervision has a significant influence on the performance of teachers SMA PGRI 1 Kota Sukabumi, In other words, the higher the supervision given, the better the performance of teachers at SMA PGRI 1 Sukabumi City.